Pengaruh Terapi Murotal Terhadap Tingkat Kecemasan Menghadapi Persalinan Pada Ibu Hamil di Wilayah Kerja Puskesmas Andalas: The Effect of Murotal Therapy on the Level of Anxiety Facing Childbirth in Pregnant Women in the Working Area of the Andalas Health Center - Riza Wahyuni; Deswita (Fakultas Keperawatan Universitas Andalas, 2013)
Anxiety is a psychological condition that is full of fear that something can be happen. In the third trimester a pregnant women was experiencing anxiety to face the labour in the future. Anxiety can have an impact on physically and psychologically in both the mother, the fetus and the labour procces. Non pharmacological management such as murotal therapy. The purpose of this research was to determine the effect of the murotal therapy on anxiety level to face the labour. The design of this reseach was quasy experiment by using one group pretest-post test approach. The subjects were 12 of pregnant women in the third trimester in Andalas Padang Publik Health Care. Taking the sampling was purposive technique. Data was collected by questionnaire and data collection was conducted from Mei 4 to Mei 18, 2013. Analyzing the data was using wilcoxon and the result of this study showed significant effect on anxiety level of pregnant women in the third trimester to face the labour with p = 0,007 (p <0,05). The effect of murotal therapy to anxiety can reduce of pregnant women in the third trimester to face the labour. It is recommended to health care institution to provide alternative therapy such as murotal therapy to reduce anxiety.